Answer:
(2, 4)
Step-by-step explanation:
To solve this system, the easiest way would be to use the substitution method. You can simply plug in, or substitute the value of y from the second equation, which is -x + 6, into the first equation. So you would get:
-x + 6 = 3x - 2
6 = 4x - 2
8 = 4x
2 = x.
To find y, just substitute the value of x, which is 2, into either equation:
y = 3(2) - 2
y = 6 -2
y = 4.
Make sure you write your answer as an ordered pair! So, the final answer is (2, 4). Hope that helped! :)